Constraints for genetic association studies imposed by attributable fraction and familial risk - Hemminki, Kari; Lorenzo Bermejo, Justo (Carcinogenesis, 2007)
Abstract. Candidate gene studies have become very popular but some of their implicit constraints, such as the familial risk and the population attributable fr